Development of Business Knowledge Sharing Program for Increasing Entrepreneurial Intention Realize Young Generation Towards a Golden Indonesia - Bachrodin, Hanis; Nasikh, Nasikh; Wardana, Ludi Wishnu (Universitas Negeri Semarang, 2024)
This study aims for know how influence Entrepreneurship education and visiting program variables industry on entrepreneurial intention which is moderated by the MSME business knowledge sharing variable among State Vocational School students in the district Jombang. The study focuses on State Vocational School students in Jombang Regency, with a sample of 155 respondents drawn from five different schools in the region. The sampling technique employed was non-probability sampling, specifically purposive sampling, ensuring that the selected participants were involved in entrepreneurship education and industry visit programs relevant to the research. Data was collected through a questionnaire consisting of 21 questions, which was distributed via directly to respondents. The data analysis was carried out using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the aid of Smart PLS 3.0 software, allowing for an in-depth examination of the relationships between entrepreneurship education, industry visit programs, and entrepreneurial intention, moderated by the MSME business knowledge sharing variable. Research result This show that entrepreneurship education and industry visit programs have an influence to entrepreneurial intention. On the side Others, entrepreneurship education and industry visit programs have an influence to entrepreneurial intention which is moderated by MSME business knowledge sharing. Conclusion of study This is an influential entrepreneurship education and industry visit program to entrepreneurial intention. MSME business knowledge sharing is capable moderate’s entrepreneurship education and industry visit programs with entrepreneurial intention.